Acquaintance of bite mark identification procedures in Forensic Odontology - Malinda, Yuti; Zakiawati, Dewi (Padjadjaran Journal of Dentistry, 2015)
Introduction: Bite mark analysis casework strives to connect a biter to the teeth pattern present on the object linked in some way to crime or event. This analysis requiring an immediate response by the forensic odontologist since the marks fade rapidly in the living and the dead in a matter of hours. The aim of this article is to help the dentist to know and understand the procedures of bite mark identification in forensic odontology field. Literature review: Bite marks may be present the following situations, a fight between adults or children, a part of sexual or physical assault by adult on children, a rape, and homosexual activities. The marks can be single or multiple, varying degrees of severity from mild marking of the tissue to deep perforation, varying location may be found on breast, face/ head, abdomen, shoulder, upper extremity, buttocks, female genitalia, male genitalia, legs, ear, nose and neck. Discussion: Dentist should master the bite mark analysis procedures. When the suspect has been recognized, the first thing to do is swabbing the oral mucosa, and then taking photographs. The next steps are preparing to take impression, and always taking notes about the procedure and the result. A soon as all the documents are completed, do the matching procedures. Delay examination will cause the lost of valuable evidence. Conclution: Dentist should carefully determine the conclusion among these possibilities , the mark is âpossible biterâ, âprobable biterâ, or âwith a high level of confidence, is the biterâ